2005
DOI: 10.1007/s10620-005-2565-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Infection in a Population of Asymptomatic People in a Checkup Unit in Mexico City

Abstract: Hepatitis C virus (HCV) infection has an estimated prevalence of 3% around the world. Unfortunately, many persons with HCV infection are asymptomatic. The aim of this study was to determine the prevalence of hepatitis C Virus infection in asymptomatic persons. This study was carried out in a population-based cross-sectional study in the Checkup Unit of University Hospital in Mexico City. Patients with two or more HCV risk factors were studied. Serum specimens from all patients were screened for HCV RNA by qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Several epidemiological studies of HCV performed in Mexican people that included blood donors, [28-30] open population, [31,32] and patients with cirrhosis [33] mentioned dental treatment as a probable risk factor. Other studies found that living with a family member infected with HCV [34,35] or suffering from liver disease [33,36,37] was an associated risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies of HCV performed in Mexican people that included blood donors, [28-30] open population, [31,32] and patients with cirrhosis [33] mentioned dental treatment as a probable risk factor. Other studies found that living with a family member infected with HCV [34,35] or suffering from liver disease [33,36,37] was an associated risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence was estimated at 1.4% in the adults and 0.95% in the total population in 2000. A considerable number of studies assessed the overall HCV prevalence (76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). In addition, two meta-analyses summarized the prevalence in different populations and geographies (5,90).…”
Section: Prevalencementioning
confidence: 99%
“…The majority of studies included sample populations from specific groups: one study examined risk factors in a sample of blood donors 24 , one involved pregnant women attending antenatal services 25 , one in homeless people 26 , one in non-PWIDs 27 , one in nurses 28 , and one in a sample of different risk groups 29 . Full details of the characteristics of the included studies are presented in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%